Interfacial growth morphologies in dense eutectic crystal mushes - Fowler, A C; Holness, Marian B (IMA journal of applied mathematics, 2023)
Abstract We consider the interfacial growth morphologies of crystals growing in contact in crystal mushes, with a specific application to those formed by the solidification of basaltic magma. We focus on the particular case of an augite (pyroxene) crystal growing between two plagioclase crystals. The augite is treated as an equant unfaceted crystal, whereas the plagioclase is faceted, and our treatment applies generally to such combinations. The resulting three-grain junctions in natural rock samples are commonly of two distinct types. In one, the two augite–plagioclase interfaces grow towards each other with opposite curvatures, whereas in the second the curvatures of the interfaces have the same sign, giving a distinctive morphology which we have called an eagle’s beak. This paper provides a theoretical framework to provide explanations for both of these morphologies, based on the kinetics of interfacial growth.